2009
DOI: 10.20965/jdr.2009.p0404
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Tsunami Force Acting on Rectangular Structures

Abstract: Hydraulic experiments were conducted to estimate tsunami wave force acting on rectangular onshore structures. Used building models placed at several distances from a shoreline. Wave pressure was measured at points on exposed structures. Impact and standing-wave pressure at different points peaked at different moments in time, so tsunami force tended to be overestimated by integrating maximum wave-pressure distribution envelope. Measured total force was thus used to formulate tsunami force estimation equations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 5 publications
2
22
0
Order By: Relevance
“…The first peak occurred when the leading edge of the bore impacted the structure, and the second peak occurred when the splashing followed with the main flow. These two peak phenomena are typical for impact loads of this type and were also observed in the experiment by Fujima et al (2009). Note that in the case of the immediate impact on the structure, no additional force is applied -for example, drag force.…”
Section: Input Loadssupporting
confidence: 69%
See 1 more Smart Citation
“…The first peak occurred when the leading edge of the bore impacted the structure, and the second peak occurred when the splashing followed with the main flow. These two peak phenomena are typical for impact loads of this type and were also observed in the experiment by Fujima et al (2009). Note that in the case of the immediate impact on the structure, no additional force is applied -for example, drag force.…”
Section: Input Loadssupporting
confidence: 69%
“…As an appropriate safety factor, Fujima et al (2009) suggests the coefficient of 1路8 in Equation 3 be increased to 3路3. These equations have resulted from small-scale physical experiments for bores propagating over a dry bed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, all the data analyzed in the present study were based on that obtained by load cell. For the hydrodynamic load of the waves on a vertical wall, it always composite by two peaks, one is due to the initial dynamic impact, and the second one is due to the reflection of run-up water (Martin et al, 1999., Fujima et al 2009. The two-peak signals were also observed from the overtopping waves.…”
Section: Observations Of Raw Datamentioning
confidence: 98%
“…Recent laboratory experiments have measured tsunami-induced water surface elevations, velocities, and pressures on and around structures and on scale models of cities, and physical models have also tested the reliability of tsunami protection structures [see Fujima et al, 2009;Bradner et al, 2009;Hsiao and Lin, 2010;Thomas and Cox, 2012;Park et al, 2013]. However, many previous experiments idealized the tsunami profile using a solitary wave [see Cox et al, 2008;Thomas and Cox, 2012;Park et al, 2013]; this solitary wave model has been shown to scale poorly to prototype tsunami time scales [Madsen et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Previous laboratory measurements of tsunami-induced pressures have recorded short duration pressure peaks corresponding with wave impact and a following quasihydrostatic pressure [see Fujima et al, 2009;Bradner et al, 2009;Thomas and Cox, 2012]. While conducting scale model experiments on highway bridge superstructures, Bradner et al [2009] found that for large-inertia structures the impulse pressure may not translate to a slamming force on structural supports.…”
Section: Introductionmentioning
confidence: 99%